Retrenchment or Expansion? : The Future of US International Campuses - Long, Kyle; Danvers, Melissa (International Higher Education, 2024)
This article examines dual forces impacting international campuses of US universities: isolationist retrenchment and neoliberal expansion. It uses the recent closure of Texas A&M University’s branch in Qatar to explore how domestic disputes are playing out internationally. It argues that the overall landscape for international campuses remains favorable to expansion, while also acknowledging worrisome trends. The analysis underscores the importance of global engagement for fostering economic growth and international cooperation.